Model Project Based Learning untuk Meningkatkan Hasil Belajar Matematika Materi Penyajian Data Kelas IV - Rozalia, Maya Ferdiana; Suwarno, Suwarno (Lembaga Penelitian dan Pendidikan Mandala, 2023)
Learning in classes that are less interesting causes learning to be held less than optimally. This has a negative impact on mathematics learning outcomes in data presentation material. This study aims to improve students' learning achievement through the application of the Project Based Learning (PjBL) learning model. This type of research is classroom action research carried out in three cycles. Each cycle consists of planning, action implementation, observation/evaluation, and reflection stages. The subjects of this study were fourth grade students at SD Negeri 1 Ternyang, totaling 23 students. Methods of data collection using tests. The test is used to measure student learning achievement after applying the Project Based Learning (PjBL) learning model. Data analysis techniques using quantitative and qualitative descriptive analysis. The results showed that there was an increase in learning outcomes at the pre-cycle stage, student learning outcomes only reached an average of 60 with a complete learning of 30.43%, in cycle I there was an average increase of 78.26 with a completeness of 78.26%, in cycle II the average increased to 84.13 with 86.96% mastery. In cycle III the average increased to 86.08 with 96.65% mastery. So the application of the Project Based Learning (PjBL) model was able to improve the learning achievement of fourth grade elementary school students. The implications of this research are expected to have a positive impact on student achievement.